(untitled) (Global Journal of Human-Social Science, 2024)
Gender-based violence GBV is a critical issue in Benin affecting women aged 15 to 49 across different departments This study examines the regional disparities in the prevalence of emotional physical and sexual violence against women as well as the rates at which they seek help to end violence Data from the fifth Demographic and Health Survey of Benin DHSB-V provides insights into the spatial distribution of GBV and the socio-demographic determinants of violence across the country Results indicate significant variations in GBV prevalence across different departments Alibori Plateau and Collines exhibit the highest rates of spousal violence while departments such as Zou and Littoral have lower rates The study also reveals disparities in helpseeking behavior with departments like Alibori and Donga showing higher rates of women seeking help and Atacora and Borgou having higher proportions of women who neither seek help nor confide in anyone about the violence they experience These findings underscore the need for targeted interventions and support programs tailored to the specific challenges of each department Addressing GBV in Benin requires a comprehensive approach that increases awareness accessibility to support services and protection for women By focusing on region-specific strategies and leveraging successful practices from lower-risk areas meaningful progress can be made toward reducing the prevalence of GBV and promoting gender equality across Benin